FORUM en scène - en video : Verslag 1984. - ten Cate, Ritsaert (Middelburg : Stichting Forum, 1985)
Abramovic, Marina & Ulay ; Baumgarten, Lothar ; Buren, Daniel ; McEvilley, Thomas ; Sheehan, Maura ; Purce, Jill ; Weiner, Lawrence ; Zaugg, Remy ; etc.
Nederlands & Engels
boek